2013
DOI: 10.1590/s1413-35552012005000116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dorsal and lateral decubitus on peak expiratory flow in healthy subjects

Abstract: | Background: One of the measures of the pulmonary function is the peak expiratory flow (PEF) that can be defined as the major flow obtained in an expiratory pressure after a complete inspiration to the level of the total lung capacity. This measure depends on the effort and strength of expiratory muscles, the airway diameter and the lung volume. Objective: To compare the results of the peak expiratory flow in healthy male and female obtained in a seated position and dorsal decubitus (DD), right lateral decubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…PEF in different body positions was evaluated in 13 studies [ 3 , 22 – 24 , 31 , 33 , 45 51 ]. Eight studies evaluated only healthy adults [ 3 , 22 – 24 , 45 , 48 , 50 , 51 ], three evaluated healthy subjects and patients with COPD or asthma [ 31 , 46 , 49 ], one included adult cystic fibrosis patients [ 47 ], and one included subjects with SCI [ 33 ]. Nine studies that compared standing or sitting positions vs. supine or RSL and LSL found higher PEF in standing and sitting [ 3 , 22 – 24 , 31 , 45 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEF in different body positions was evaluated in 13 studies [ 3 , 22 – 24 , 31 , 33 , 45 51 ]. Eight studies evaluated only healthy adults [ 3 , 22 – 24 , 45 , 48 , 50 , 51 ], three evaluated healthy subjects and patients with COPD or asthma [ 31 , 46 , 49 ], one included adult cystic fibrosis patients [ 47 ], and one included subjects with SCI [ 33 ]. Nine studies that compared standing or sitting positions vs. supine or RSL and LSL found higher PEF in standing and sitting [ 3 , 22 – 24 , 31 , 45 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluated only healthy adults [ 3 , 22 – 24 , 45 , 48 , 50 , 51 ], three evaluated healthy subjects and patients with COPD or asthma [ 31 , 46 , 49 ], one included adult cystic fibrosis patients [ 47 ], and one included subjects with SCI [ 33 ]. Nine studies that compared standing or sitting positions vs. supine or RSL and LSL found higher PEF in standing and sitting [ 3 , 22 – 24 , 31 , 45 48 ]. Three of six studies comparing the standing and sitting positions found higher PEF in standing [ 46 , 50 , 51 ] and one reported higher PEF in sitting [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gianinis et al (18) compared the Peak Expiratory Flow (PEF) by spirometry in 30 young and healthy individuals in sitting position, SP, RLD and LLD. It has been proven statistically significant differences in sitting position, SP and RLD.…”
Section: Discussionmentioning
confidence: 99%
“…A avaliação pré-operatória utiliza testes funcionais que possuem papel chave no diagnóstico e determinação da gravidade do distúrbio respiratório e na determinação da melhor conduta ao paciente com afecções pulmonares, sendo capazes de quantificar as alterações observadas nos pacientes e traduzirem sua real condição física e pulmonar (GIANINIS et al, 2013).…”
Section: Cirurgia Cardíaca E Avaliação Pré-operatóriaunclassified